Seasonal pattern of rotation‐affected internal seiches in a small temperate lake. (14th June 2013) - Bernhardt, Juliane; Kirillin, Georgiy
Abstract : The aim was to disclose the seasonality in the internal seiches during summer stratification in 2010 within the small, 3 km long, ellipse‐shaped, temperate Lake Arendsee (Germany) with simple morphometry. We used observations of temperatures from two thermistor chains (09 April to 24 September), conductivity and temperature profiles, and wind speeds and directions (January to December). To analyze the seasonality in the periods, appearance and modal structure of the seiches, and the wind forcing, we applied spectral analysis on monthly time series of isotherms and wind speeds, and wavelet analysis on 6 month long time series of integrated potential energy and wind speeds. To determine the effect of earth's rotation on seiches, we applied two analytical models based on three‐layer density stratification. Earth's rotation affected internal seiches significantly even in a small lake. That was shown by the models and the Burger number being < 1 during stratification. Vertical mode 1 Kelvin‐type seiches dominated the internal seiche weather in Lake Arendsee, with their periods changing because of seasonal variations in stratification. Weak, free seiches of vertical mode 2 were amplified during three episodes: (1) in mid‐summer, when their periods coincided with the inertial period at the lake's latitude, (2) in late spring, and (3) in autumn, both when their periods approached 24 h. The amplifications were caused by resonance between free seiches and wind‐forced oscillations at diurnal and inertial periods. Such short‐term resonance events, associated with enhanced mixing, are inherent for the seasonal stratification cycle in the most temperate lakes.